2019
DOI: 10.3390/nu11040828
|View full text |Cite
|
Sign up to set email alerts
|

Food-Insecure Household’s Self-Reported Perceptions of Food Labels, Product Attributes and Consumption Behaviours

Abstract: Dietary compromises related to food insecurity profoundly undermine health and constitute a serious public health issue, even in developed nations. The aim of this study was to explore the impact of food labelling and product attributes on the purchasing choices of food-insecure households in Australia. An online survey containing 19 food choice and 28 purchasing behaviours questions was completed by 1056 adults responsible for household grocery shopping. The short form of the US Household Food Security Survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 38 publications
3
19
0
1
Order By: Relevance
“…The results also suggest that HFI was associated with lower level of food label literacy. Consistent with our observation Butcher et al found Australian households with low or very low HFI status less tend to find, use or be influenced by nutrition information on food labels when making dietary decisions [14]. Similarly, Gittelsohn et al reported the lowest food label reading and food knowledge scores among food-insecure households in Baltimore City in the USA [16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results also suggest that HFI was associated with lower level of food label literacy. Consistent with our observation Butcher et al found Australian households with low or very low HFI status less tend to find, use or be influenced by nutrition information on food labels when making dietary decisions [14]. Similarly, Gittelsohn et al reported the lowest food label reading and food knowledge scores among food-insecure households in Baltimore City in the USA [16].…”
Section: Discussionsupporting
confidence: 90%
“…Findings from some recent studies have shown that in comparison to the food-secure households, those with food insecurity had lower FNLIT mainly characterized by unfavorable food choices and purchasing decisions as well as poor food preparation skills [13][14][15][16]. However, this evidence was limited to the adult population living in high-income and developed countries; thus, it is unknown whether these findings are generalizable to the children and adolescents particularly in the low-income and developing nations.…”
Section: Introductionmentioning
confidence: 99%
“…The results also suggest that HFI was associated with lower level of food label literacy. Consistent with our observation Butcher et al found Australian households with low or very low HFI status less tend to nd, use or be in uenced by nutrition information on food labels when making dietary decisions (14). Similarly, Gittelsohn et al reported the lowest food label reading and food knowledge scores among foodinsecure households in Baltimore City in the USA (16).…”
Section: Discussionsupporting
confidence: 89%
“…Findings from some recent studies have shown that in comparison to the food-secure households, those with food insecurity had lower FNLIT mainly characterized by unfavorable food choices and purchasing decisions as well as poor food preparation skills (13)(14)(15)(16). However, this evidence was limited to the adult population living in high-income and developed countries; thus, it is unknown whether these ndings are generalizable to the children and adolescents particularly in the low-income and developing nations.…”
Section: Introductionmentioning
confidence: 99%
“…Social determinants of health such as socio-economic status and household income are associated with food purchasing decisions and dietary intake, whereby households of lower income and those in rural and remote areas often have poor diet quality and greater risk of disease [20][21][22]. Barriers such as the price of fresh produce and lack of cooking skills can influence purchasing behaviours for healthier foods, especially among lower socio-economic families and those who are food insecure [23][24][25]. Therefore providing individuals, families and communities with food literacy and access to information to develop budgeting skills, efficient food shopping strategies, and skills to prepare healthy meals at low cost, may overcome economic barriers that presently prevent healthy eating [26,27].…”
Section: Introductionmentioning
confidence: 99%